Contact Resistance between Calcareous Sand and Electrodes Based on the Two-Electrode Method - Weikang Wan; Heying Hou; Tianxiang Li; Binghui Wang; Pengming Jiang; Aizhao Zhou (Geofluids)
In the process of measuring the resistivity of calcareous sand by the two-electrode method, the contact resistance between calcareous sand and electrodes is an unavoidable problem. In this paper, the effects of the particle size, relative density, current frequency, and saturation on the contact resistance of calcareous sand samples with different electrode spacings were studied. The results show that the larger the particle size and relative density are, the greater the contact resistance. The contact resistance decreases with an increasing current frequency, and the decreasing amplitude decreases with an increasing saturation. The contact resistance decreases with an increasing saturation. The relationship between the contact resistance and current frequency and saturation is established in this paper. When the two-electrode method is used to study the resistivity of calcareous sand, the influence of contact resistance should be considered, especially for samples with low saturation.